Health risk assessment of lead and cadmium contamination in raw cow’s milk from eastern Algeria - Meriem Imen Boussadia; Ali Boudebbouz; Sofiane Boudalia; Mohamed Amine Kerdoun; Rabah Zebsa; Zinette Bensakhri; Atoussi Sadek (Environmental Research Communications)
To assess potential health risks from heavy metal exposure through raw cow’s milk, we investigated lead (Pb) and cadmium (Cd) levels in milk samples from eastern Algeria using atomic absorption spectrometry and estimated dietary risks for adults and children. In 2021, 99 milk samples were collected from various regions. Average Pb and Cd levels were 0.332 ± 0.097 and 0.016 ± 0.011 mg kg ^−1 , respectively, with Pb exceeding the MRL in 99% and Cd in 87% of samples. Estimated daily intake (EDI) values for both metals were below established limits, indicating acceptable average exposure levels. However, the Target Hazard Quotient (THQ) and Hazard Index (HI) assessments revealed significant concerns. For adults, THQ and HI remained below 1, and carcinogenic risk (CR) values for Pb were below 10 ^−4 . In children, Cd posed minimal risk (THQ < 1), but Pb was problematic. While average THQ for Pb was below 1, 39% of samples exceeded this limit. HI for both metals surpassed 1 in 51% of samples, and CR for Pb exceeded 10 ^−4 in 17 samples. These findings highlight the need for further analysis of milk from various Algerian regions to ensure consumer safety.